FINANCIAL CONTROLLING: ORGANIZATIONAL AND METHODOLOGICAL FUNDAMENTALS FORMATION AND FUNCTIONING AT THE ENTERPRISE - SYDORCHUK, Ivanna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes modern definitions of the "financial controlling" categories. The principles of organization of financial controlling at the enterprise are formulated. Blocks and elements of the financial controlling mechanism are defined. The main stages of financial controlling in the process of managing the financial and economic activities of the enterprise are highlighted. A methodical approach to the formation of a system of indicators for controlling the success of the enterprise is proposed. Financial controlling is a control system that ensures the concentration of control actions on the most priority areas of financial activity, the timely detection of deviations of its actual results from the planned ones and the adoption of operational management decisions regarding the normalization of the financial activities of the enterprise. It is advisable to present the process of financial controlling in the enterprise management system in the form of the following main stages: problem finding, problem recognition, information processing, decision-making, financial plans, implementation of plans. In this case, at each stage of the management process, a defining controlling system can be identified. Thus, the search for the problem consists in the accounting of existing data on the state of the financial sphere of the enterprise, which involves conducting a comprehensive assessment of the financial indicators of the enterprise, which can be obtained on the basis of financial accounting, as a controlling system. Selection and formation of the system of indicators of the enterprise in the financial sphere of its activity includes: liquidity; profitability; Cash Flow; capital structure; asset structure; accounts receivable; accounts payable; financial relations with investors; real investments; financial investments; turnover of current assets. Each sector of the economy has its own specific set of organizational and economic, technical, personnel, social and financial features that affect the use of controlling tools. In our opinion, it is appropriate to use a comprehensive approach to the content of controlling.